2015
DOI: 10.1002/ppap.201500143
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Deposition of Plasma‐Polymerized Polyacrylic Acid and Silver Nanoparticles for the Production of Nanocomposite Coatings Using a Non‐Equilibrium Atmospheric Pressure Plasma Jet

Abstract: A single step process for the deposition of nanocomposite coatings with silver nanoparticles (AgNPs) embedded in a plasma-polymerized polyacrylic acid (pPAA) matrix and performed using a non-equilibrium atmospheric pressure plasma jet is presented. Acrylic acid (AA) and AgNPs dispersed in ethanol (EtOH) are used as precursors and are separately injected in the plasma region directly; Ar is used as plasma gas and also as carrier gas for both precursors. Scanning electron microscopy (SEM) and ATR-FTIR analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Indeed the incorporation of TiO2 nanoparticles in polypyrrole, polythiophene or polyfuran matrix allowed an increase of the conductivity of the composite coating. For biomedical application, Gherardi and co-workers [21] showed a significant antibacterial activity of the nanocomposite coatings obtained by incorporating silver nanoparticles embedded in plasma polymerized polyacrylic acid matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed the incorporation of TiO2 nanoparticles in polypyrrole, polythiophene or polyfuran matrix allowed an increase of the conductivity of the composite coating. For biomedical application, Gherardi and co-workers [21] showed a significant antibacterial activity of the nanocomposite coatings obtained by incorporating silver nanoparticles embedded in plasma polymerized polyacrylic acid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore Prasai et al [22] reported that thin multilayers of pure graphene grown by CVD on nickel slowed down its corrosion rate by 20 times as compared to the uncoated one. Several papers have reported the beneficial effect of incorporating graphene or graphene oxide sheets in composites to enhance the corrosion properties of metals [3][4][5][19][20][21][22][23]. Ramezanzadeh et al [27] developed a nanocomposite coating based on silane with functionalized graphene oxide (fGO), by sol-gel before depositing a 100 µm thick epoxy protective layer.…”
Section: Introductionmentioning
confidence: 99%
“…A one‐step process has been optimized by Palumbo et al for the plasma deposition of nanometric hydrophilic biocomposite coatings embedding active Lysozyme, an antimicrobial enzyme. The deposition method is developed in an Atmospheric Pressure Plasma (APP) reactor in Dielectric Barrier Discharge (DBD) configuration, coupled with an atomizer to feed the gas discharge low vapor pressure pure liquids, salts solutions, and suspensions of nano‐particles . This configuration allows the deposition on any kind of flat substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Plasma pre-treatment of the PLLA solution allowed to obtain bead-free fibers and mats with good mechanical properties. Similarly, in this work, the exposure of the PVdF electrospinning solution to an atmospheric pressure plasma jet, previously described in, [31,32,[35][36][37][38] permits the production of defect free fibers and good quality PVdF separators, easy to handle also after imbibition in the electrolyte. Moreover, plasma post-treatment of the obtained electrospun PVdF separators is performed by means of a nanosecond pulsed dielectric barrier discharge (DBD) operating in ambient air.…”
Section: Introductionmentioning
confidence: 99%